2004
DOI: 10.1897/03-336
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics of three polychlorinated biphenyl technical mixtures in rainbow trout (Oncorhynchus mykiss)

Abstract: Accumulation and depuration parameters of polychlorinated biphenyls (PCBs) in fish have been reported only for a few congeners. As well, there is little information on the ability of fish to biotransform PCBs. To address these issues, juvenile rainbow trout (Oncorhynchus mykiss) were exposed to dietary concentrations of three Aroclor mixtures (1248, 1254, 1260) in food for 30 d followed by an additional 160 d of nonspiked food at 8 degrees C. Accumulation, depuration, and potential biotransformation of 92 PCB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
69
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 44 publications
16
69
0
Order By: Relevance
“…The mean difference between predicted (without biotransformation) and experimental values was very low (14%). These considerations support the conclusion that for these pollutants, biotransformation processes in whitefish are very limited, according to Buckman et al (2004). Plotting the experimental and predicted (without biotransformation) relative increase values versus Log K ow data (Fig.…”
Section: Age-dependent Modelsupporting
confidence: 79%
See 1 more Smart Citation
“…The mean difference between predicted (without biotransformation) and experimental values was very low (14%). These considerations support the conclusion that for these pollutants, biotransformation processes in whitefish are very limited, according to Buckman et al (2004). Plotting the experimental and predicted (without biotransformation) relative increase values versus Log K ow data (Fig.…”
Section: Age-dependent Modelsupporting
confidence: 79%
“…In animals several transformation processes have been described. Generally much lower biotransformation rates were observed in fish than in birds and mammals (Boon et al 1989;Buckman et al 2004). On the basis of the substitution pattern, three groups of congeners were proposed by Boon et al (1989): those without a free chlorine meta-para position and more than 1 ortho-Cl (persistent congeners); those with a free chlorine ortho-meta position on at least one of phenyl rings, and no more than 1 ortho-Cl (potentially biotransformed); and those with a free chlorine meta-para position on at least one of phenyl rings, and more than 1 ortho-Cl (readily biotransformed).…”
mentioning
confidence: 99%
“…The selected period (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) may be deemed too long in this respect, according to the PCB depuration ability of some fish species. Half-lives of 1-4 months in rainbow trout (Niimi and Oliver 1983), 6-7 months in juvenile rainbow trout (Fisk et al 1998;Buckman et al 2004), and 12-24 months in guppy (Poecilia reticulata) (Sijm et al 1992) have been reported. Nevertheless, these experiments were conducted on young fish at constant (and optimal) temperatures, for relatively short periods of time.…”
Section: Sqg Calculationmentioning
confidence: 99%
“…Even though fish are generally not considered to be capable of efficient biotransformation of PCBs (Boon et al, 1989;Buckman et al, 2004), considerable concentrations of hydroxylated PCBs (OH-PCBs) and methylsulfone PCBs (MeSO 2 -PCBs), two kinds of PCB metabolites derived from Phase I and/or Phase II biotransformation, have been detected in deepwater sculpin (Myoxocephalus thompsoni, 7.04 ± 5.47 ng/g lipid wt of MeSO 2 -PCBs) and lake trout (Salvelinus namaycush, 0.02e0.44 ng/g wet wt of OH-PCBs) collected from the Great Lakes (Campbell et al, 2003;Stapleton et al, 2001), and in northern snakehead (Channa argus, 5.82 ± 0.23 ng/g wet wt of OH-PCBs, and 43e370 ng/g lipid wt of MeSO 2 -PCBs) and mud carp (Cirrhinus molitorella, 0.15 ± 0.03 ng/g wet wt of OH-PCBs, and 58e16 g/g lipid wt of MeSO 2 -PCBs) from an e-waste recycling area in South China (Zeng et al, 2014a;Zhang et al, 2012). Previous work demonstrated that fish do have some capacity to biotransform PCBs (Buckman et al, 2006;Fisk et al, 1998;Wong et al, 2002).…”
Section: Introductionmentioning
confidence: 99%